Afectaciones psicológicas que presentan los internos desde la percepción de los guardas de seguridad de un Instituto penitenciario de la ciudad de Cartago Valle (2023)
The present investigation focuses on describing an analysis about the perception of the psychological conditions presented by the inmates of a penitentiary institute in the city of Cartago, Valle, interpreted by 2 Dragoneantes officials belonging to the National Prison and Penitentiary Institute, residents of the municipality of Carthage, Valley.